Ordered Amorphous Carbon: New Ordered Structure of Amorphous Carbon Clusters Induced by Fullerene–Cubane Reactions (Adv. Mater. 22/2018). Issue 22 (May 2018) - Du, Mingrun; Yao, Mingguang; Dong, JiaJun; Ge, Peng; Dong, Qing; Kováts, Éva; Pekker, Sándor; Chen, Shuanglong; Liu, Ran; Liu, Bo; Cui, Tian; Sundqvist, Bertil; et al.
Abstract : In article number1706916, Bingbing Liu and co‐workers report new amorphous carbon clusters constructed ordered materials by compressing C60 /cubane co‐crystals, which is induced by the reactions between the stiff fullerene and highly energetic cubane. A new strategy can thus be developed for material design by tailoring the boundary interactions of the amorphous building blocks using highly energetic matter.